α-Synuclein in Parkinson’s disease: causal or bystander? - Riederer, Peter; Berg, Daniela; Casadei, Nicolas; Cheng, Fubo; Classen, Joseph; Dresel, Christian; Jost, Wolfgang; Krüger, Rejko; Müller, Thomas; Reichmann, Heinz; Rieß, Olaf; Storch, Alexander; et al. (Journal of Neural Transmission, 2019)
Parkinson’s disease (PD) comprises a spectrum of disorders with differing subtypes, the vast majority of which share Lewy bodies (LB) as a characteristic pathological hallmark. The process(es) underlying LB generation and its causal trigger molecules are not yet fully understood. α-Synuclein (α-syn) is a major component of LB and SNCA gene missense mutations or duplications/triplications are causal for rare hereditary forms of PD. As typical sporadic PD is associated with LB pathology, a factor of major importance is the study of the α-syn protein and its pathology. α-Syn pathology is, however, also evident in multiple system atrophy (MSA) and Lewy body disease (LBD), making it non-specific for PD. In addition, there is an overlap of these α-synucleinopathies with other protein-misfolding diseases. It has been proven that α-syn, phosphorylated tau protein (pτ), amyloid beta (Aβ) and other proteins show synergistic effects in the underlying pathogenic mechanisms. Multiple cell death mechanisms can induce pathological protein-cascades, but this can also be a reverse process. This holds true for the early phases of the disease process and especially for the progression of PD. In conclusion, while rare SNCA gene mutations are causal for a minority of familial PD patients, in sporadic PD (where common SNCA polymorphisms are the most consistent genetic risk factor across populations worldwide, accounting for 95% of PD patients) α-syn pathology is an important feature. Conversely, with regard to the etiopathogenesis of α-synucleinopathies PD, MSA and LBD, α-syn is rather a bystander contributing to multiple neurodegenerative processes, which overlap in their composition and individual strength. Therapeutic developments aiming to impact on α-syn pathology should take this fact into consideration.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Autophagy; Gene expression; Lysosome; Neuroinflammation; Neuromelanin; Parkinson’s disease; Proteasome; Protein interactions; SNCA gene; Synucleinopathy; Therapy; α-Synuclein